African theology in the intellectual journey of Alioune Diop - (:unkn) unknown (My University, 2015)
In the aftermath of the Second World war, the emergence of many intellectual movements including Présence Africaine founded by Alioune Diop in 1947, led to many intellectual productions. It is in this wake that one can situate the African theology, which remains an important dimension of the dynamics of Christianity in Africa.
Keywords: African Research